Akuntansi Pemerintahan di Indonesia suatu Tinjauan - Indra Firmansyah Bagjana (Jurnal Akuntansi, 2008)
Indonesian people more critical after reformation in Indonesia. One of criticized object is accountability and transparency in government financial management. Government Accounting Standard is one of tool that can measure of government financial management performance. This Paper would like to explain several aspect that relate to government accounting in Indonesia, that is : financial management, challenges, comparison betweengovernment accounting and commercial accounting, unique case of government accounting, development strategy, and career opportunity for accountant in government organization.Keyword : Government Accounting